1994
DOI: 10.1002/macp.1994.021950628
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation on heating of undercooled melt of poly(ethylene oxide)‐urea molecular complex

Abstract: X-ray and calorimetric investigations of the structure and transformations on heating of quenched (undercooled) samples of poly(ethy1ene oxide)-urea molecular complexes are discussed. It was established that at room temperature the undercooled melt of the molecular complex contains free urea in a tetragonal crystal modification and a high-temperature poly(ethy1ene oxide)-urea molecular complex whose crystal modification does not coincide with the known hexagonal crystal structure of the molecular complex obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, when the quenched samples are heated to 90 °C, the usual trigonal crystal modification, stable at room temperature, reappeared. 16 PEG-U-IC was investigated using X-ray diffraction previously by Suehiro et al It was suggested that all the reflections in the PEG-U-IC diffractogram can be indexed with a large tetragonal unit cell with unit cell dimension of a ) b ) 9.3 Å and c ) 19.51 Å. However, to date there is no report on the structural determination of PEG-U-IC single crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the quenched samples are heated to 90 °C, the usual trigonal crystal modification, stable at room temperature, reappeared. 16 PEG-U-IC was investigated using X-ray diffraction previously by Suehiro et al It was suggested that all the reflections in the PEG-U-IC diffractogram can be indexed with a large tetragonal unit cell with unit cell dimension of a ) b ) 9.3 Å and c ) 19.51 Å. However, to date there is no report on the structural determination of PEG-U-IC single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that heating the trigonal crystal form to 150 °C and then quenching to 0 °C yields a crystal form different from the usual trigonal or hexagonal crystal structure. However, when the quenched samples are heated to 90 °C, the usual trigonal crystal modification, stable at room temperature, reappeared …”
Section: Resultsmentioning
confidence: 99%
“…[12,13] By virtue of inter-species hydrogen bonding between the constituent polar molecules, the melting temperatures of the α crystals in the intermediate PEO/urea blend compositions were found to be considerably higher than those of the neat constituents. [14,15] Upon lowering temperature, there appeared another compound called β crystal in the PEO-rich region that melts in the vicinity of ~100 o C, i.e., intermediate between those of neat PEO crystal (i.e., 65 o C) and of the α crystal (i.e., 144 o C). [16][17][18] The β crystal was characterized as a metastable crystal that transformed reversibly to the stable α crystal upon heating and cooling.…”
Section: Introductionmentioning
confidence: 99%